Mortality Due to Subarachnoid Hemorrhage from 1999 to 2003. - Javier García Zacarías; Eduardo Hernández Ortiz; José M. Carles Zerquera; Cecilia Zacarías Chialjub; Ángel Luis Zayas Luis (Medisur)
Background: Subarachnoid hemorrhage represents from the 6 to 8 per cent of all ictus. Its prevalence is calculated in 10 cases per 100.000 persons a year. It is accompanied by frequent complications and a high level of lethality. Objectives: To characterize deceased patients who had suffered from this disease from the pathological and clinical standpoint in a 5 year-period of time from 1999 to 2003. Method: A descriptive retrospective study was carried out including all patients deceased due to subarachnoid hemorrhage to whom necropsy was performed in the University Hospital ¨Camilo Cienfuegos¨, in Sancti Spiritus from 1999 to 2003. Results: 51 cases were analyzed where the white female sex was predominant, and who were older than 75 years old. The most important clinical antecedent or history was hypertension. The majority of admissions were carried out in the intensive care unit. The most important complications were cerebral edema with endocrania hypertension, and bronchopneumonia. Two thirds of the deaths were neurological where cerebral edema with endocrania hypertension and herniation followed by bronchopneumonia were predominant. Conclusions: Patients with extreme age, hypertensives were predominant. Cerebral edema with endocrania hypertension, hernia, and low respiratory sepsis were the algorithm of the complications and the cause of death.